Underlying mechanisms and physiology of muscular power - Kraemer, W. J. (Strength and Conditioning Journal, 2012)
The underlying basis of power is the optimal recruitment of motor units that allow for the needed force at a given velocity of movement. Power is an important physical capability for any athlete in today's competitive sports. Power is expressed for any movement ranging from 0 w in isometric muscle actions to more than 10,000 w in a vertical jump. The neuromuscular system that supports these arrays of power production outcomes is dependent upon a variety of physiological characteristics (e.g., muscle fiber types) and mechanisms (e.g., size principle). Proper program design is dependent upon understanding the physiological basis of power.